2006
DOI: 10.1080/09603100500426374
|View full text |Cite
|
Sign up to set email alerts
|

Technical trading strategies and cross-national information linkage: the case of Taiwan stock market

Abstract: This study tests four prevalent moving average technical trading rules for Taiwan stock markets. More notably, cross-national information from the US stock markets is also incorporated in our technical trading rules to project Taiwan stock market movements. We then design trading strategies and investigate their predictive power over buy-and-hold strategy. Our results suggest that technical trading rules are predictive for Taiwan stock markets. Applying the information reflected in the US stock markets to proj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Chang et al (2004) find profitable trading opportunities in a number of Asian emerging markets. Chang et al (2006) find that technical trading rules have predictive power for the Taiwan equity market.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Chang et al (2004) find profitable trading opportunities in a number of Asian emerging markets. Chang et al (2006) find that technical trading rules have predictive power for the Taiwan equity market.…”
Section: Introductionmentioning
confidence: 87%
“…Chang et al . () find that technical trading rules have predictive power for the Taiwan equity market.…”
Section: Introductionmentioning
confidence: 93%
“…For stock market studies see Goldberg and Schulmeister (1988), Brock, Lakonishok, and LeBaron (1992), Hudson, Dempsey, and Keasey (1996), Gunasekarage and Power (2001), Fernandez‐Rodriguez, Gonzalez‐Martel, Sosvilla‐Rivero (2000, 2005), Kwon and Kish (2002), Wong, Manzur, and Chew (2003), Jasic and Wood (2004), Chang, Metghalchi, and Chan (2006). “Abnormal” returns of technical analysis in foreign exchange markets are reported by Schulmeister (1988), Levich and Thomas (1993), Menkhoff and Schlumberger (1995), Gencay and Stengos (1998), Chang and Osler (1999), Neely and Weller (1999), Gencay (1999), LeBaron (1999), Osler (2000), Maillet and Michel (2000), Neely and Weller (2003), Okunev and White (2003), Schulmeister (2008a,b).…”
mentioning
confidence: 99%
“…For example, Kwon and Kish (2002) confirmed that technical trading rules can add a value to capture profit opportunities over a buy and hold strategy for the NYSE value-weighted index. Metaghachi and Chang (2003) and Chang, Metghalchi & Chan (2006) applied various moving average rules to conclude the profitability of technical trading in the Italian and the Taiwanese stock markets. Wong, Manzur & Chew (2003) investigated the Singapore data to indicate that the moving average and the relative strength index (RSI) can be used to generate significantly positive return.…”
Section: Literature Reviewmentioning
confidence: 99%